The Analysis Of Particle Size Distribution (PSD) After Blasting Using Aerial Photography At Fys Marketing Sdn. Bhd., Bukit Mertajam, Penang - Johari, Nurrahman (Universiti Sains Malaysia, 2018)
Previous researches conducted the fragmentation analysis by capturing images of the muck pile using digital camera at eye-level point of view. Therefore, this research is dedicated for analyzing the Particle Size Distribution after blasting using aerial photography as a new approach. This is to compare the results of taking digital images of the muck pile at eye-level point of view from aerial point of view. The introduction of Unmanned Aerial Vehicle (UAV) to this research which act as a device for aerial photography and not to mention Fotor Photo Editor software is to enhance the images taken to ensure good results when being analyzed using WipFrag 2010 software. Throughout findings, different point of view for image capturing can show different results. At aerial view, it shows strong consistency of results when being analyzed to the Particle Size Distribution graph. Not to mention, at any direction or angle when the being done using aerial photography, the Particle Size Distribution graph remains consistent. Furthermore, if the digital image is being enhanced with a better quality, the Particle Size Distribution graph shows a more accurate result. Therefore, through this study, there will be a much better understanding on the effect of using aerial point of view compared to an eye-level point of view on the Particle Size Distribution (PSD) graph. Not only that, this study also proves that with the introduction of technology to Mineral Resources industry, new researches and findings can be obtained to achieve and excel more in this industry.